Preliminary experience of endoscopic submucosal tunnel dissection for upper gastrointestinal submucosal tumors - Gong, W.; Xiong, Y.; Zhi, F.; Liu, S.; Wang, A.; Jiang, B. (Endoscopy, 2012)
Background and study aim: Although the majority of submucosal tumors (SMTs) are benign, some do have a malignant potential. Resection of SMTs would aid in establishing the diagnosis and may be curative. Our aim was to examine the feasibility and safety of a novel method for endoscopic resection of upper gastrointestinal SMTs.Patients and methods: In 12 patients who presented with an upper gastrointestinal SMT of ≤ 40 mm located in the esophagus or cardia, a submucosal tunnel was endoscopically created starting approximately 5 cm proximal to the lesion. After careful submucosal dissection with carbon dioxide or air insufflation, the SMTs were completely removed, and the entrance of the tunnel closed using endoclips. Results: SMTs had a mean size of 19.5 mm (range 10 – 40 mm); eight were located in the esophagus and four in the cardia. SMT resection was successful in all patients with en bloc resection in 10 patients (83.3 %) and resection in two pieces in the remaining two patients. The mean time required for the procedure was 48.3 minutes (range 30 – 60 minutes). Two patients had both pneumothorax and subcutaneous emphysema. All the complications resolved with conservative management. Conclusions: In this pilot study, endoscopic submucosal tunnel dissection (ESTD) of esophageal and cardia SMTs was effective and appeared to be safe. Larger studies that also examine its application for gastric SMTs are warranted.